Understanding Behavioral Intent to Participate in Shared Decision-making in Medically Uncertain Situations - Maffei, R. M.; Dunn, K.; Zhang, J.; Hsu, C. E.; Holmes, J. H. (Methods of Information in Medicine, 2012)
Objective: This article describes the process undertaken to identify and validate behavioral and normative beliefs and behavioral intent based on the Theory of Reasoned Action (TRA) and applied to men between the ages of 45 and 70 in the context of their participation in shared decision-making (SDM) in medically uncertain situations. This article also discusses the preliminary results of the aforementioned processes and explores potential future uses of this information that may facilitate greater understanding, efficiency and effectiveness of clinician-patient consultations.Materials and Methods: Twenty-five male subjects from the Philadelphia community participated in this study. Individual semi-structure patient interviews were conducted until data saturation was reached. Based on their review of the patient interview transcripts, researchers conducted a qualitative content analysis to identify prevalent themes and, subsequently, create a category framework. Qualitative indicators were used to evaluate respondents’ experiences, beliefs, and behavioral intent relative to participation in shared decision-making during medical uncertainty.Results: Based on the themes uncovered through the content analysis, a category framework was developed to facilitate understanding and increase the accuracy of predictions related to an individual’s behavioral intent to participate in shared decision-making in medical uncertainty. The emerged themes included past experience with medical uncertainty, individual personality, and the relationship between the patient and his physician. The resulting three main framework categories include 1) an individual’s Foundation for the concept of medical uncertainty, 2) how the individual Copes with medical uncertainty, and 3) the individual’s Behavioral Intent to seek information and participate in shared decision-making during times of medically uncertain situations.Discussion: The theme of Coping (with uncertainty) emerged as a particularly critical behavior/characteristic amongst the subjects. By understanding a subject’s disposition with regard to coping, researchers were better able to make connections between a subject’s prior experiences, their knowledge seeking activities, and their intent to participate in SDM. Despite having information and social support, the subjects still had to cope with the idea of uncertainty before determining how to proceed with regard to shared decision-making. In addition, the coping category reinforced the importance of information seeking behaviors and preferences for shared decision-making.Conclusions: This study applies and extends the field of behavioral and health informatics to assist medical practice and decision-making in situations of medical uncertainty. More specifically, this study led to the development of a category framework that facilitates the identification of an individual’s needs and motivational factors with regard to their intent to participate in shared decision-making in situations of medical uncertainty.
Keywords: Medical uncertainty; behavioral intent; shared decision-making